The Big Book How To Draw - "NA" (Mumbai Wilco Publishing house, 2010)
The big book of how to draw is the perfect way to get you started on drawing cool and funky pictures. Appealing illustrations on interesting subjects such as Animals, Actions, Fairytales characters, and Birds.